2021
DOI: 10.1097/qai.0000000000002888
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Bictegravir/Emtricitabine/Tenofovir Alafenamide Efficacy in Participants With Preexisting Primary Integrase Inhibitor Resistance Through 48 Weeks of Phase 3 Clinical Trials

Abstract: Session: P-24. Clinical Trials Background: VIR-2482 is a fully human immunoglobulin G1(IgG) monoclonal antibody (mAb) directed against a highly-conserved epitope in the influenza A hemagglutinin stem region and is in clinical development for the prevention of influenza A illness. The Fc region of VIR-2482 has been modified to provide an extended half-life.Methods: This is a randomized, placebo-controlled, Phase 1/2 study of VIR-2482 administered intramuscularly (IM) to healthy adult volunteers aged 18-64 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…1 , 10 This combination was often selected due to favorable tolerability profile of the BIC/FTC/TAF component, ability to retain partial NRTI activity in the patients for which it was prescribed, and due to the high barrier to resistance of bictegravir. 11 A pooled analysis of phase 3 clinical trial data by D’Antoni et al 11 found that a small cohort of patients with primary INSTI resistance achieved or maintained virologic suppression through 48 weeks of BIC/FTC/TAF treatment. Pre-existing INSTI mutations were detected in 20 of the 1907 participants, and all but one of these 20 participants was virologically suppressed at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , 10 This combination was often selected due to favorable tolerability profile of the BIC/FTC/TAF component, ability to retain partial NRTI activity in the patients for which it was prescribed, and due to the high barrier to resistance of bictegravir. 11 A pooled analysis of phase 3 clinical trial data by D’Antoni et al 11 found that a small cohort of patients with primary INSTI resistance achieved or maintained virologic suppression through 48 weeks of BIC/FTC/TAF treatment. Pre-existing INSTI mutations were detected in 20 of the 1907 participants, and all but one of these 20 participants was virologically suppressed at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…11 A pooled analysis of phase 3 clinical trial data by D'Antoni et al Antoni et al11 reinforced our confidence in utilizing BIC/FTC/TAF as part of our simplification strategies. While there is limited guidance regarding bictegravir use in treatmentexperienced patients with drug resistance and in combination with other antiretroviral agents, we feel that our experience could help guide clinicians when multi-class combinations are needed with efforts to reduce pill burden.…”
mentioning
confidence: 92%
“…16 Bictegravir/emtricitabine/tenofovir alafenamide in people with HIV who have underlying genotypic resistance In one study of individuals who had pre-existing INSTI resistance mutations with one primary INSTI-resistant substitution, including E92G, Y143C/H, S147G, Q148H/K/R, N155S or R263K, and some with secondary substitutions, 19 out of 20 individuals who were virologically suppressed successfully maintained virologic suppression when switched to BIC/FTC/TAF. 18 Additionally, BIC/FTC/TAF has been shown to be effective in individuals with NRTI-resistance associated mutations. In a study of PWH, of whom almost half carried the M184V/I resistance mutation and 21 out of 29 had more than one NRTI-resistance associated mutation, 49 out of 50 PWH had undetectable viral loads after over 18 months on treatment with BIC/FTC/ TAF.…”
Section: Optimizing Antiretroviral Therapy For People With Hiv/hepati...mentioning
confidence: 99%
“…Injectable formulations of PrEP, notably long-acting cabotegravir, have recently been found in randomised controlled trials to be efficacious for preventing HIV acquisition 11. Despite this, there have been concerns regarding new models of adherence with long-acting PrEP, and the spectre for potential integrase-inhibitor resistance in the setting of missed acute HIV infection with starting long-acting PrEP or resistance surrounding early stoppage of injectable PrEP 12 13. Additionally, certain patient populations may not accept a long-acting injectable PrEP formulation, or may experience adverse events at the injection site that may limit their use 14.…”
Section: Introductionmentioning
confidence: 99%